Inhibition of catechol-O-methyltransferase by natural pentacyclic triterpenes: structure-activity relationships and kinetic mechanism - Fang-Yuan Wang; Gui-Lin Wei; Yu-Fan Fan; Dong-Fang Zhao; Ping Wang; Li-Wei Zou; Ling Yang (Taylor & Francis Group, 2021)
Inhibitors of COMT are clinically used for the treatment of Parkinson's disease. Here, we report the first natural pentacyclic triterpenoid-type COMT inhibitors and their structure-activity relationships and inhibition mechanism. The most potent compounds were found to be oleanic acid, betulinic acid and celastrol with IC50 values of 3.89-5.07 μM, that acted as mixed (uncompetitive plus non-competitive) inhibitors of COMT, representing a new skeleton of COMT inhibitor. Molecular docking suggested that they can specifically recognise and bind with the unique hydrophobic residues surrounding the catechol pocket. Furthermore, oleanic acid and betulinic acid proved to be less disruptive of mitochondrial membrane potential (MMP) compared to tolcapone, thus reducing the risk of liver toxicity. These findings could be used to produce an ideal lead compound and to guide synthetic efforts in generating related derivatives for further preclinical testing.